Metode AHP Untuk Sistem Pendukung Keputusan Sekolah Sadar Lalu Lintas - Joko Siswanto; I Made Suartika; Rahadian Satya Mahaddhi (SOTVI - Society of Visual Informatics, 2024)
Traffic conscious school covers various aspects that influence the effectiveness and accuracy of traffic education program evaluation. A structured and comprehensive approach is needed involving all stakeholders to update and adapt the traffic conscious school strategy to suit needs and developments. DSS is proposed to support traffic conscious school decisions using the website based AHP method. DSS was built adopting the XP Model with planning, design, coding and testing stages. Planning consists of functional and non functional requirements. The design contains application designs and AHP calculation designs with a CR value of 0,04 for 5 criteria 4 sub criteria, which means they are consistent. The highest priority value is 048 for the teacher and human environment criteria, while the lowest is for the object environment criteria. The test results show there is no difference between manual calculations and the proposed system. DSS can support stakeholder decisions to adopt traffic conscious school policies and strategies.